NOR A WAY : Young Art from Norway. - Friede, Claus; Brockmann, Jan; Herbstreuth, Peter; Nievers, Knut; Stadtgalerie im Kulturviertel/Sophienhof, Kiel (Kiel : Nieswand Verlag, 1997)
Christensen, Jeannette ; Lange, Andrea ; Ness, Ole Jorgen ; Olofsson, Anneè ; Pahlsson, Sven ; Rodland, Torbjorn ; Tandberg, Vibeke.
Noraway Young Art from Norway, Stadtgalerie im Kulturviertel/Sophienhof, Kiel, 16. August - 28. September 1997
kunstcatalogus